Evaluation of the Implementation of Minimum Service Standards (SPM) of BPJS Kesehatan in Palangka Raya from the Perspective of the Local Community - Annelies Veny Demak; Selvia Martha (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the experiences of the community in utilizing BPJS Kesehatan (BPJS Health) at public health centers (puskesmas) and hospitals in Palangkaraya City, based on interviews with patients and health service officers. A qualitative approach was used, applying in?depth interviews, and the data were analyzed thematically. The results show that BPJS Kesehatan is generally perceived to facilitate access to health services from a financial perspective, especially for people with limited income. Patients reported feeling more confident to seek care at puskesmas and hospitals because much of the cost is covered by the National Health Insurance program (JKN). In hospitals, patients are usually asked first whether they will use BPJS or pay privately, but the administrative procedures and queuing systems are often perceived as long and confusing. Some respondents also reported a lack of clarity regarding which services are covered by BPJS and which must be paid out of pocket. Overall, BPJS Kesehatan in Palangkaraya is considered to ease access to health services, but there is still a need for improvement in administrative systems, coordination among facilities, and public education so that BPJS utilization becomes more efficient and comfortable.